Capitellidae (Annelida) na plataforma continental de Sergipe, nordeste do Brasil : estrutura da comunidade e do habitat - Souza, José Weverton Santos de (2018)
Biological communities have patterns of abundance, richness, diversity and composition determined by environmental filters or stochastic factors that may lead to species substitution or nesting. Capitellidae is a family of marine worms (Polychaeta), common on the coast of Brazil, that inhabits several environments due to the high tolerance to environmental gradients and for which there is little ecological information. In this study, a survey of the Capitellidae taxa of the Sergipe Continental Shelf (SCS) was carried out and the spatial-temporal variation of the ecological descriptors was verified, looking for which mechanism (turnover or nestedness) structures this community besides investigating how and which environmental variables influence this structuring. During the dry and rainy periods (2001 to 2003) samples were taken along the SCS in three isobaths (10, 20 and 30m), sampling the trawl dredge and Van Dorn bottle water. The sedimentological material was conserved in ice for granulometric analysis of OM and CaCO3 contents and in 10% formalin for the faunistic analysis. The community of Capitellidae was composed of 1,096 individuals distributed in 50 taxa grouped into 13 genera and 11 morphotypes. Of these taxa, three are new species for science (Notomastus sp. 8, Scyphoproctus sp. 4 and Capitellidae sp. 7), five new genera with occurrence for Brazil (Amastigos, Pseudoleiocapitella, Dasybranchetus, Neonotomastus and Mastobranchus) and 49 new occurrences for Sergipe. Four taxa were distinguished by abundance: Notomastus hemipodus, Notomastus latericeus, Notomastus lobatus and Mediomastus sp. The composition of the species among the sediment spots did not change significantly due to the high behavior of species. Gravel patches harbored greater abundance and richness (p<0.05). The environmental parameters presented temporal oscillations for the water variables, being the rainy season with the highest temperature and salinity (p<0.05). Spatially the water variables showed no variation (p>0.05). The sediment texture showed no temporal variation (p>0.05), but varied spatially (p<0.05), the isobaths differing from 30m in the others regarding the degree of selection and grain size, percentages of organic matter and CaCO3 and gravel and silte contents. On the other hand, the community structure was stable without fluctuations for the ecological descriptors (p>0.05). Spatially abundance, richness, diversity and equitability showed an increasing pattern towards deeper areas (p<0.05). The composition of the fauna oscillated both in time (p=0.00; R = 0.08) and in space (p=0.02; R=0.12). These oscillations were due to the temporal (βTUR = 0.43; βNES = 0.08) and spatial (βTUR = 0.46; βNES = 0.25) substitution mechanisms that determined the high β temporal diversity (βJAC = 0.51) and spatial (βJAC = 0.72). The relationship of the environmental variables with the fauna evidenced the sediment variables as the main structurers of the communities. Depth influenced all descriptors (p=0.00); the degree of grain selection exerted influence on the diversity and equitability (p=0.04); grain size (p=0.01) and CaCO3 content (p=0.005) influenced abundance and gravel influenced the richness (p=0.02). The results obtained allow us to infer that SCS is an environment with high richness of Capitellidae, which is distributed in heterogeneous bottoms, causing species substitution along the environmental gradient with increasing descriptors in deeper areas.